Infiltrative Optic Neuropathies: Opening Doors to Sinister Pathologies. (3rd September 2017) - Takkar, Aastha; Naheed, Darakshan; Dogra, Mohit; Goyal, Manoj K.; Singh, Ramandeep; Gupta, Nalini; Gupta, Kirti; Mittal, B. R.; Lal, Vivek
ABSTRACT: Optic disc edema may be caused by a number of conditions. A commonly ignored but important aspect is the presence of "infiltration" of disc; that may closely mimic disc edema. Disc edema, optic nerve dysfunction and a normal appearing disc in any combination may occur in infiltrative optic neuropathies. Identifying disc infiltration can aid in diagnosis of many sinister pathologies even in the absence of other specific clinical features. We describe two patients presenting with optic nerve dysfunction and infiltrated disc appearance, which on investigations were found to have underlying malignancies thereby underscoring the importance of detecting infiltrative optic neurpathies.